2020
DOI: 10.1021/acs.biochem.0c00107
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Allosteric Coupling between Substrate Binding and Adx Recognition in the Vitamin D Carbon-24 Hydroxylase CYP24A1

Abstract: Metabolic inactivation of 1,25(OH) 2 D3 requires molecular recognition between the mitochondrial enzyme cytochrome P450 24A1 (CYP24A1) and its cognate redox partner adrenodoxin (Adx). Recent evidence supports a model of CYP24A1 function in which substrate binding and Adx recognition are structurally linked. However, the details of this allosteric connection are not clear. In this study, we utilize chemical crosslinking coupled to mass spectrometry, nuclear magnetic resonance (NMR) spectroscopy, and CYP24A1 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…More recently, Ivanov and associates used surface plasmon resonance (SPR) to estimate K d values for POR and Adx interactions with 12 different P450s [12]. The effect of substrate binding on the P450-Adx complex has been examined recently both by SPR [13] and solution NMR [14,15]. Solution NMR indicated that substrate binding altered the interaction of microsomal P450 17A1 with another auxiliary protein, cytochrome b 5 [16], which is consistent with more recent SPR studies [13].…”
Section: Introductionsupporting
confidence: 55%
“…More recently, Ivanov and associates used surface plasmon resonance (SPR) to estimate K d values for POR and Adx interactions with 12 different P450s [12]. The effect of substrate binding on the P450-Adx complex has been examined recently both by SPR [13] and solution NMR [14,15]. Solution NMR indicated that substrate binding altered the interaction of microsomal P450 17A1 with another auxiliary protein, cytochrome b 5 [16], which is consistent with more recent SPR studies [13].…”
Section: Introductionsupporting
confidence: 55%
“…We have previously reported on the presence of long-range communication between the active site and the proximal Adx-binding surface of the corresponding interaction in rCYP24A1. 13,14 An interesting feature of hCYP24A1 is that, in contrast to other mitochondrial CYPs, 24,25 titration with unfused hAdx alone does not introduce a detectible high-spin character of the heme (Figure S2). This is also true for the spectra of the uncleaved hCYP24A1-hAdx protein.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Mutation of adrenodoxin Leu80 to lysine nearly abolished 11β-hydroxylase activity in both CYP11B enzymes ( 14 ). Conversely, for vitamin D 3 -metabolizing rat CYP24A1, the mutation L80K led to a tighter binding of adrenodoxin and did not abolish enzyme activity ( 33 ). In CYP11B1, mutation of the conserved Val441 to glycine is reported to abolish cortisol production in patients ( 34 ) and this could also be due to decreased interactions.…”
Section: Discussionmentioning
confidence: 99%